BENTUK DAN PENGGUNAAN PRONOMINA PERSONA BAGI MAHASISWA STKIP BANJARMASIN (THE FORM AND USE OF PERSONAL PRONOUNS BY STKIP STUDENT IN BANJARMASIN) - Eka Suryatin (Balai Bahasa Sulawesi Utara, 2016)
This study discusses the forms and variations in the use of personal pronouns by STKIP students in Banjarmasin. The purpose of this study is to describe the forms and variations in the use personal pronouns by STKIP students in Banjarmasin. This research is a qualitative descriptive study. The data collection is obtained by observation techniques, see, and record. Research data are in the form the speech used by STKIP students in Banjarmasin, Department of PBSID (Local or Indonesian Language and Literature Education). The results show that the using personal pronouns are three forms, namely the first person, second person, and third person. Based on the type of reference personal pronoun used by STKIP students in Banjarmasin are singular and plural pronoun.When it is viewed from the morphological distribution, there are a full form and a short form. The short forms are usually used in proclitic (appears before its host) and also enclitic (appear after its host). Personal pronouns used by the students in their speech are varied. Although they are in Banjar, they do not only use personal pronouns in Banjar language, a part of the students use the first person singular pronoun gue ‘aku’. Personal pronouns in Banjar language used by the STKIP students in Banjarmasin are the first person singular pronoun, ulun, unda, sorang, saurang and aku. First person singular pronoun aku has some variations –ku and ku- that are bound morpheme. First person plural is kami and kita. The second person pronouns are pian, ikam, nyawa, and kamu. Meanwhile, the third person singular pronouns are Inya and Sidin. The third person plural pronoun is bubuhannya. The use of personal pronouns by STKIP students in Banjarmasin are dominantly consist of five speech components only that are based on the situation, the partner, the intent, the content of the message, and how the speaker tells the speech.